Gender preference at birth: A new measure for son preference based on stated preferences and observed measures of parents' fertility decisions - Mehwish Ghulam Ali; Ashton De Silva; Sarah Sinclair; Ankita Mishra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Investigating preference for sons is a continuing focal area of development economics and demographic research. Son preference presents a challenge in achieving the United Nations Sustainable Development Goals of 'no poverty', 'good health and wellbeing', and 'gender equality' by 2030. It is thus important to investigate son preference to inform policy-makers of the potential challenges in achieving these goals. Inaccurate interpretation of the mechanisms of son preference could misinform policy analysis and result in unintended consequences. Existing measures including sex ratios and gender composition of children do not reflect the true extent of son preference in high fertility countries such as Pakistan, where the success of policy action is limited and significant barriers to sex-selective technologies exist. Given the likely impact of son preference on fertility behaviour in Pakistan, accurate measurement of the forms this gender bias can take is necessary to appropriately gauge the influence of son preference on the fertility outcomes. The limited capacity of existing measures to accurately depict son preference in countries with high fertility combined with limited demarcation between pre- and post-birth son preference warrants development of a new measure for son preference to evaluate its effects. In this paper, a new measure of son preference called 'gender preferences at birth' (GPB) is presented. GPB combines stated fertility preferences and observed fertility outcomes to acknowledge that households in countries with high fertility and low contraception usage have less control over their fertility decisions.
Keywords: J13; I31; J16; 330; fertility; family planning; general welfare; wellbeing; economics of gender